Measuring health-related beliefs of mothers of adolescent and young adult childhood cancer survivors - Doshi, Kinjal (2011)
Childhood cancer has long-term implications for survivors and their family members. While the impact of cancer on the family continues into adulthood, little research exists on family-related issues during this important developmental period. In order to advance our understanding of families of adolescent and young adult (AYA) childhood cancer survivors, a measure of health-related beliefs for parents of AYA cancer survivors was developed. Exploratory factor analysis based on the mothers' data was used to identify four factors among 23 items: Social Competence, Satisfaction with Healthcare, Health Perceptions, and Health Apprehension. The scales are associated with psychological distress, quality of life, and posttraumatic stress symptoms but unrelated to age of the child at diagnosis and cancer treatment intensity. The beliefs identified in this study are consistent with clinical observations of families of young adult survivors and provide indications for the importance of ongoing attention to the families of childhood cancer survivors.